Pendidikan Toleransi Antar Siswa Beragama Hindu Dan Islam di SD Negeri 3 Keramas Kecamatan Blahbatuh Kabupaten Gianyar - Purniati, Kadek; Sariani Binawati, Ni Wayan (Jayapangus Press, 2024)
Tolerance education is an important aspect in building a harmonious social life in Indonesia, especially in areas with religious diversity such as Gianyar. Tolerance education is becoming increasingly important in the midst of increasing intolerance and religious polarization in Indonesia. This phenomenon can be seen from the rise of cases of discrimination, hate speech, and violence on the basis of religion. This research uses a qualitative approach with a case study method. Data were collected through participant observation, interviews, and document analysis. The data were analyzed using qualitative analysis techniques. The results of this study outline that: First, the form of tolerance between Hinduism and Islam at SD Negeri 3 Keramas is in the form of: social activities, religious activities, in school relationships, cultural arts activities, sports activities at school, and group learning activities. Second, the obstacles faced in the application of tolerance in SD Negeri 3 Keramas, Blahbatuh District, Gianyar Regency are fanaticism, limited coaching, and exclusivism. Third, the efforts made to strengthen tolerance between Hinduism and Islam at SD Negeri 3 Keramas, Blahbatuh District, Gianyar Regency are to impose sanctions on religious harassment, get guidance from all teachers, understand other religions more comprehensively, prioritize dialogue as a discourse to be tolerant to teachers and students at SD Negeri 3 Keramas. The dialogue aims so that teachers and students can build understanding and mutual understanding, not to win, the dialogue given is always about mutual respect, understanding other religions, being polite, not demonizing other religions and certainly increasing the attitude of tolerance that has existed since long ago at school.